Edukasi Gizi Seimbang untuk Peningkatan Kesehatan Anak di Desa Cigoong, Serang, Banten - Setiadi, Adi; Ayuningtyas, Vidya; Ginanjar, Gigin; Handayani, Wuri; Mahroji, Mokhamad; Hidayat, Arif; Nur Fatimah, Andini (IMPACT: Journal of Community Service, 2025)
Children's health is greatly influenced by a healthy diet. One way to achieve this is through education on balanced nutrition. This community service program aims to enhance the knowledge of the people in Cigoong Village, Serang, Banten, about the importance of balanced nutrition for children's health. The method used includes direct counseling and practical demonstrations on selecting and preparing healthy food. The results indicate that participants experienced an approximately 40% increase in their knowledge of balanced nutrition, which is expected to influence children's eating habits in the village. Thus, this program has a positive impact on children's nutritional status and the overall health of the Cigoong Village community.